Pembuatan Game 2D Melawan Virus Menggunakan Unity Engine - Nur Affandi, Amam; Budiman, Budiman (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
A game or game is something that can be played with certain rules so that there are winners and there are losers, usually in a context that is not serious with the purpose of refreshing. Various games include; action, action-adventure, simulation, construction, and management, role playing games (RPG), strategy, racing, sports, puzzles, and word games. To create a digital game, a game engine designed to develop video games on various platforms is required. The Unity Engine can be used to create 2D (two-dimensional) and 3D (three-dimensional) games and supports a wide range of cross-platform devices such as smartphones, PCs, PlayStation 5, and many other platforms. In this study, the researcher wants to implement the creation of a 2D game called LAVIR using the GDLC (Game Development Life Cycle) method. The creation of this game aims to reduce anxiety, fear and eliminate boredom.